Blinatumomab-driven T-cell activation in αβ and γδ T-cell subsets: insights from in vitro assays - Kelm, Miriam; Nasr, Nourhan; Bendig, Sonja; Kabelitz, Dieter; Lustig, Marta; Trautmann, Heiko; Laqua, Anna; Peters, Christian; Wesch, Daniela; Oberg, Hans-Heinrich; Janssen, Ottmar; Valerius, Thomas; et al. (Frontiers in Immunology, 2026)
IntroductionBlinatumomab (BLN) is a bispecific T-cell engager that has revolutionized the treatment of B-cell precursor acute lymphoblastic leukemia (BCP-ALL), significantly improving outcomes in both adults and children. By simultaneously binding to CD19 on B cells and CD3 on T cells, BLN triggers target cell-dependent T-cell activation, resulting in the cytolysis of CD19+ BCP-ALL cells. Despite the remarkable clinical advancements achieved with BLN, the immunological mechanisms underlying treatment response or failure remain poorly characterized. γδ T cells are attractive candidates for adoptive T-cell therapy due to potent cytotoxicity, capacity to present antigens, broad lysis of different tumor entities, and low alloreactivity. Because γδ T cells can also be redirected by BLN, we systematically studied BLN-driven effector functions in vitro in conventional αβ and unconventional γδ T cells from healthy donors.Materials and methodsWe evaluated cytotoxicity and cytokine/effector release in freshly isolated and in vitro-expanded αβ and γδ T cells from healthy adults against CD19+ BCP-ALL cell lines (NALM-6, HAL-01), and profiled dynamic phenotypic alterations by multiparametric flow cytometry.ResultsCD19+ targets were consistently reduced in the presence of BLN. Freshly isolated αβ, especially CD8+, displayed superior BLN-mediated effector functions as compared to γδ T cells, with donor-dependent variability in γδ killing. Notably, zoledronate-expanded Vγ9Vδ2 γδ T-cell lines achieved cytotoxicity comparable to PHA-expanded αβ cells. However, γδ T-cell-killing benefited from higher BLN concentration when challenged with high tumor load. In these in vitro healthy-donor T-cell cultures, BLN induced CD3 down-modulation in αβ T cells but not in γδ T cells, and αβ cultures released higher soluble Fas ligand, findings consistent with stronger early activation and suggestive of increased susceptibility to activation-associated apoptosis/AICD. Exploratory targeted single-cell transcriptomics (one donor) supported a pronounced activation/exhaustion program in αβ T cells and a comparatively stable effector-memory profile with low checkpoint expression in γδ T cells.DiscussionTogether, these in vitro data reveal subset-specific BLN responses and support the hypothesis that ex vivo-expanded Vγ9Vδ2 γδ T cells could complement BLN-mediated cytotoxicity, particularly under conditions of higher CD19 density and lower target burden. These findings provide a mechanistic framework for future testing of γδ T-cell/BLN combination strategies in patient-derived models and clinical studies.